cis and trans Isomers distinguished by imidazole N-alkylation after Debus-Radziszewski reaction starting from 2,7-di-tert-butyl-pyrene-4,5,9,10-tetraone - Ma, Bin-Bin; Peng, Yu-Xin; Zhao, Pei-Chen; Huang, Wei (Tetrahedron, 2015)
We report the design and synthesis of three new imidazo[5,4-f]2,7-di-tert-butyl-pyrene-imidazol derivatives prepared from 2,7-di-tert-butylpyrene-4,5,9,10-tetraone and respective aromatic aldehyde through Debus-Radziszewski reaction. It is noted that three pairs of cis and trans isomers (1–6) can be separated after double imidazole N-alkylation for the central fused imidazole/pyrene/imidazole core, because of their distinguishable molecular polarity and improved solubility. Successful separation of every cis and trans isomeric pair can be verified by the single-crystal structural and spectral proofs. To the best of our knowledge, the current study is the first structural and spectral investigation on the imidazole N-alkylation of imidazole/pyrene/imidazole based compounds after successful separation of cis and trans isomers. [Display omitted] Three pairs of cis and trans isomers with fused imidazole/pyrene/imidazole based compounds have been successfully separated after double imidazole N-alkylation, and they can be distinguished by 1H NMR spectra and X-ray single-crystal structures.